Clinical and Electrophysiological Differentiation between Periodical and Epileptic Discharges - Podlepich, Vitaliy V.; Savin, Ivan A. (Journal of Neuroanaesthesiology and Critical Care, 2020)
Clinical differentiation between nonconvulsive status epilepticus (NCSE) and encephalopathy remains challenging. Some patients with encephalopathy exhibit periodic discharges on electroencephalography. In certain cases, however, it is rather difficult to differentiate between epileptic and periodic discharges. The lack of clear differentiation criteria makes it difficult to effectively analyze the studies in this field. In patients with refractory status epilepticus, the wrong diagnosis can lead to insufficient therapy, thereby increasing the frequency of convulsions and the likelihood of a poor outcome. Alternatively, aggressive therapy with antiepileptic drugs and anesthetic agents can aggravate neuronal damage and worsen encephalopathy. In this review, we aimed to determine whether clinical and instrumental methods can be used to differentiate between encephalopathy and epileptic states, to improve the selection of the appropriate treatment strategies. The review considers different approaches to diagnosing encephalopathy and seizures in critically ill patients. In spite of electroencephalography (EEG) still being the main method used to objectively identify brain dysfunction and diagnose epileptic discharges over the past 60 years, improvements in EEG techniques have been accompanied by increase in our understanding of the limitations of electrophysiological methods, leading to the use of additional tools for the differential diagnosis of seizures and encephalopathy. Current studies aim to develop multimodal approaches to the differential diagnosis of encephalopathy and NCSE. Modern reports describe clinical and instrumental approaches for accurately differentiating encephalopathy and epileptic conditions in patients treated in the intensive care unit based on clinical data, EEG, magnetic resonance imaging, positron emission tomography, biochemical analyses, and immune values.
Keywords: Ictal-interictal continuum; periodic discharges; nonconvulsive status epilepticus